2010
DOI: 10.1002/cne.22430
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin expression in the developing and adult murine brain

Abstract: Frontotemporal lobar degeneration (FTLD) is a neurodegenerative condition characterized by focal degeneration of the frontal and temporal lobes of the brain. Autosomal dominantly inherited mutations of the progranulin gene (GRN) have been identified as the cause of a subset of cases of familial FTLD. In order to better understand the function of progranulin in the central nervous system (CNS), we have assessed the spatiotemporal expression pattern of both the murine progranulin gene (Grn) and the protein (Grn)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 53 publications
5
110
1
Order By: Relevance
“…PGRN can be processed to granulin (GRN) peptides (4), which may have different functions (5). PGRN is expressed widely in tissues and circulates in the blood and cerebrospinal fluid (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…PGRN can be processed to granulin (GRN) peptides (4), which may have different functions (5). PGRN is expressed widely in tissues and circulates in the blood and cerebrospinal fluid (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…PGRN is normally expressed in a large number of neuronal populations in the adult CNS (Petkau et al, 2010); however, acute and chronic insults to the CNS, including neurodegenerative disorders such as FTD, result in a dramatic upregulation of PGRN in microglia, suggesting that PGRN may play a key role in regulating the neuroinflammatory response Matzilevich et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…In the adult brain, PGRN is expressed in microglia, in pyramidal neurons of the cortex and hippocampus, as well as in cerebellar Purkinje cells and spinal motor neurons (Petkau et al, 2010). PGRN has been shown to play a role in promoting neuronal survival, enhancing neurite outgrowth and regulating inflammation in the central nervous system (CNS) (Guo et al, 2010;Ryan et al, 2009;Tang et al, 2011;Van Damme et al, 2008;Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Progranulin (PGRN) is a multifunctional secreted growth factor that is widely expressed in the developing brain but becomes progressively restricted to defined neuronal populations, including cortical and hippocampal pyramidal neurons and Purkinje cells (Daniel et al, 2000(Daniel et al, , 2003Petkau et al, 2010). Thus far, PGRN has been implicated in the regulation of neuronal survival (Van Damme et al, 2008;Ryan et al, 2009;Kleinberger et al, 2010), and treatment of neurons with exogenous PGRN has been shown to enhance neurite outgrowth (Van Damme et al, 2008;Gao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%